Perspectives on simulation-based training from paediatric healthcare providers in Nigeria: a national survey - Veronica Chinyere Ezeaka; Ireti B Fajolu; Beatrice N Ezenwa; Patricia Akintan; Emeka Chukwu; Chuck Spiekerman (BMJ Open, 2020)
ObjectivesThe objective of this study was to explore the access to, and perceived utility of, various simulation modalities by in-service healthcare providers in a resource-scarce setting.SettingPaediatric training workshops at a national paediatric conference in Nigeria.ParticipantsAll 200 healthcare workers who attended the workshop sessions were eligible to participate. A total of 161 surveys were completed (response rate 81%).Primary and secondary outcome measuresA paper-based 25-item cross-sectional survey on simulation-based training (SBT) was administered to a convenience sample of healthcare workers from secondary and tertiary healthcare facilities.ResultsRespondents were mostly 31–40 years of age (79, 49%) and women (127, 79%). Consultant physicians (26, 16%) and nurses (56, 35%) were in both general (98, 61%) and subspecialty (56, 35%) practice. Most had 5–10 years of experience (62, 37%) in a tertiary care setting (72, 43%). Exposure to SBT varied by profession with physicians more likely to be exposed to manikin-based (29, 30% physicians vs 12, 19% nurses, p<0.001) or online training (7, 7% physician vs 3, 5% nurses, p<0.05). Despite perceived barriers to SBT, respondents thought that SBT should be expanded for continuing education (84, 88% physician vs 39, 63% nurses, p<0.001), teaching (73, 76% physicians vs 16, 26% nurses, p<0.001) and research (65, 68% physicians vs 14, 23% nurses, p<0.001). If facilities were available, nearly all respondents (92, 98% physicians; 52, 96% nurses) would recommend the use of online simulation for their centre.ConclusionsThe access of healthcare workers to SBT is limited in resource-scarce settings. While acknowledging the challenges, respondents identified many areas in which SBT may be useful, including skills acquisition, skills practice and communication training. Healthcare workers were open to the use of online SBT and expressed the need to expand SBT beyond the current scope for health professional training in Nigeria.